2002
DOI: 10.1046/j.1444-2906.2002.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Total activity of transglutaminase at various temperatures in several fish meats

Abstract: Transglutaminase seems to be related to the setting phenomenon of fish meat paste that occurs at temperatures below 40°C. In many reports on the relationship between transglutaminase and setting phenomenon, the enzyme activity has been measured at 25°C. However, it is known that the setting phenomenon is complicated and the effect of calcium and the 3‐D structure of myofibrils, which are sensitive to temperature, play important roles in the reaction. In the present study, total activities of transglutaminase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…7a) showed no heavy molecular weight (HMW) bands (N 200 kDa) formation in any sample due to protein cross-linking, indicating no activity of inherent transglutaminase in this type of fish muscle under these conditions. Transglutaminase is known to be widely distributed in fish meats (Nozawa, Mamegoshi, & Seki, 1999); however, its activity varies depending on conditions, from fish to fish (Tsukamasa, Miyake, Ando, & Makinodan, 2002).…”
Section: Protein-protein Interactionsmentioning
confidence: 99%
“…7a) showed no heavy molecular weight (HMW) bands (N 200 kDa) formation in any sample due to protein cross-linking, indicating no activity of inherent transglutaminase in this type of fish muscle under these conditions. Transglutaminase is known to be widely distributed in fish meats (Nozawa, Mamegoshi, & Seki, 1999); however, its activity varies depending on conditions, from fish to fish (Tsukamasa, Miyake, Ando, & Makinodan, 2002).…”
Section: Protein-protein Interactionsmentioning
confidence: 99%
“…The optimal temperature ensuring the maximum activity of the enzyme also depends on its origin. TGase from carp and bream fl esh is the most active at 50°C, whereas that from the fl esh of threadfi n breams (Nemipterus virgatus) and white croaker (Genyonemus lineatus) -at 40 and 30°C, respectively [Tsukamasa et al, 2002]. These authors showed also that TGase from different sources retained at least 80% of its maximum activity at 37°C.…”
Section: Effect Of High Pressure Treatment On Transglutaminase Activitymentioning
confidence: 54%
“…92 Worratao and Youngsawatdigul 93 reported that optimum temperature and optimum pH of tilapia TGase were 37-50 • C and 7.5, respectively. The maximal TGase activity of carp meat (88.5 U g −1 sample) was found at 50 • C, followed by threadfin bream (28.4 U g −1 meat) at 40 • C, white croaker (19.7 U g −1 meat) at 30 • C and red sea bream (17.1 U g −1 meat) at 50 • C. 89 Therefore, the setting can be maximized based on the pH and temperature profile of individual fish species.…”
Section: Endogenous Tgasementioning
confidence: 99%
“…Total TGase activity differs depending on the temperature of measurement. 89 Optimum temperatures of TGase vary with species such as threadfin bream (55 • C), 90 red sea bream (Pagrus major) (55 • C), 91 bigeye snapper (Priacanthus tayenus) (40 • C) and bigeye snapper (Priacanthus macracanthus) (25 • C). 92 Worratao and Youngsawatdigul 93 reported that optimum temperature and optimum pH of tilapia TGase were 37-50 • C and 7.5, respectively.…”
Section: Endogenous Tgasementioning
confidence: 99%